Allegorical readers and cultural revision in ancient Alexandria - Dawson, David, 1957- (University of California Press, 1992)
"Allegorical readings always being as counter-readings, starting with denial or negation: "You have read the text this way, but I will read it differently." But allegory may do more than merely challenge the literal sense--it may also revise prevailing cultural ideals and social practices. In this book, David Dawson combines literary interpretation, social history of religion, and intellectual history to describe how some ancient pagan, Jewish, and Christian interpreters used allegory to endorse, revise, and subvert competing worldviews. Rather than insist, as do standard discussions, that ancient allegory is best understood as a way of reading texts, Dawson considers allegory as a way of using nonliteral readings to reinterpret culture and society. He argues that the Jewish and Christian allegorical readers of ancient Alexandria were not merely turning scriptural language into ciphers for Hellenistic meanings. On the contrary, they were attentive to the textuality of the works they interpreted and to the socio-historical worlds in which they lived. Rather than trying to assimilate scripture to the dominant culture, they aimed at cultural revision through allegorical readings." "Focusing on works by the Stoic philosopher Cornutus and the literary critic Heraclitus, the book opens with an analysis of the pagan use of etymology and allegory in the Hellenistic world and discusses pagan opposition to both techniques. The remainder of the book presents three Hellenistic religious writers who each typify distinctive models of allegorical interpretation: the Jewish exegete Philo, the Christian Gnostic Valentinus, and the Christian Platonist Clement." "In addition to contributing directly to the fields of classics, history of Christianity, and history of Hellenistic Judaism, this study of ancient allegory will be of interest to scholars engaged in literary criticism and theory, as well as to those concerned more broadly with critical theory and cultural criticism. Dawson's new approach to allegorical reading, emphasizing socio-cultural context rather than purely formal literary features, will contribute toward the contemporary reassessment of this ancient interpretive practice."--Jacket.